The Wreck of the William Brown : - Koch, Tom (International Marine, 2004)
Seventy-one years before the loss of the Titanic, another ship sank in almost the same spot after striking an iceberg at maximum speed. Three-quarters of the passengers—poor, mostly Irish emigrants—were lost, including at least fourteen who were thrown from a lifeboat to lighten it. Not a single sailor died.